Some Thoughts on the Natural Regeneration of Sal (Shorea robusta) in U.P. - Srivastava, P. B. L. (Indian Forester, 1969)
Current ideas on the problem of natural regeneration of sal in U.P. have been summarised. The results of the work done during the last decade or so to determine the growth requirements of sal seedling. have been briefly stated. A summary of diecussions held during the last Silvicaltural Conference (1967) and fature coarse of work in order to understand the nature, causes and other fundamental aspects of problem have been given.